Faktor Internal Penyebab Mahasiswa Menunda Mengerjakan Tugas Akhir Pada Mahasiswa D-III Reguler - Elita Dwi Kusuma Astuti; Wiworo Haryani; Aryani Widayati (Journal of Oral Health Care, 2017)
The final task is Scientific Writing prepared by Diploma III students according to Indonesian rules, under the supervision or direction of supervisors to get the criteria. Quality of the criteria that have been set in accordance with their each respective knowledge. One of the requirements to become a diploma graduate of three dental nursing department Poltekkes Kemenkes Yogyakarta must complete the final task of Scientific Writing, done in the sixth semester. This research aims to determine the internal factors causing students in doing the final task/scientific writing in D-III Regular students of dental nursing Poltekkes Kemenkes Yogyakarta academic year 2016/2017. This research used descriptive research method with data retrieval method using questionnaire. This research was conducted in the dental nursing department campus with total respondents as many as 39 subjects. From the result of the research, it is found that the internal factors that cause the students in doing the final task/scientific writing are divided into 2 categories. The first is psychological factors, consisting of anxiety (63,2%), laziness (42,1%), fear of failure (21,1%), perfectionism (13,2%), time management(10,5%) and perception (0%). And the second is physical factor (81,6%). The most severe factor to the level of desire in doing on the final task is physical factor with a percentage of 81,6%.